2014
DOI: 10.1371/journal.pone.0098163
|View full text |Cite|
|
Sign up to set email alerts
|

The Form of a Conditioned Stimulus Can Influence the Degree to Which It Acquires Incentive Motivational Properties

Abstract: There is considerable individual variation in the extent to which food- and drug-associated cues (conditioned stimuli, CSs) acquire incentive salience, as indicated by whether they elicit approach towards them, and/or act as conditioned reinforcers. Here we asked whether this variation is influenced by properties of the CS itself. In rats, we assessed both the attractiveness and conditioned reinforcing properties of two CSs: a manipulable lever CS versus an auditory (tone) CS. There was considerable individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
90
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 83 publications
(95 citation statements)
references
References 82 publications
5
90
0
Order By: Relevance
“…Like others (Holland 1977;Cleland and Davey 1983;Holland et al 2014;Meyer et al 2014) the present results demonstrate clearly that different conditioned stimuli can preferentially elicit sign-and goal-tracking, and these stimuli can be differentially attributed with incentive salience or value. However, the current within-subject method is a departure from the predominant method used to study sign-and goal-tracking behavior in the past.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Like others (Holland 1977;Cleland and Davey 1983;Holland et al 2014;Meyer et al 2014) the present results demonstrate clearly that different conditioned stimuli can preferentially elicit sign-and goal-tracking, and these stimuli can be differentially attributed with incentive salience or value. However, the current within-subject method is a departure from the predominant method used to study sign-and goal-tracking behavior in the past.…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, Meyer et al (2014) demonstrated that a reward-predictive tone that elicits goal-tracking behavior maintains the same amount of conditioned reinforcement in animals prescreened as sign-trackers or goal-trackers, while the lever stimulus associated with sign-tracking was the most robust conditioned reinforcer. Importantly, Meyer et al (2014) also demonstrated that the conditioned reinforcement maintained by the tone in sign-and goal-trackers was equivalent to that maintained by a lever in animals prescreened as goal-trackers. Collectively, these results indicate that a tone associated with goal-tracking and a lever associated with goal-tracking are of equivalent value, maintaining identical conditioned reinforcement regardless of whether an animal is labeled as a sign-tracker or goal-tracker.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Taken together, these results suggest GTs more readily rely on contextual cues, and STs on discrete or punctate cues, irrespective of extinction training or the motivational valence or associative nature (instrumental or Pavlovian) of the setting. However, it remains to be determined exactly what psychological propensities give rise to such variation in the ability of various classes of environmental stimuli to gain control over motivated behavior (see also Meyer et al, 2014). Although we have emphasized a motivational interpretation here, we readily acknowledge there are a number of other interacting processes that could contribute to such variation, from visuospatial (Hickey et al, 2010;Hickey and van Zoest, 2012) to attentional processes, to variation in the content of learning (Clark et al, 2012).…”
Section: Individual Differences In Control Exerted By Different Typesmentioning
confidence: 95%